AKUNTABILITAS LEMBAGA KESEJAHTERAN SOSIAL DI DAERAH ISTIMEWA YOGYAKARTA - Sugiyanto Sugiyanto (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2021)
Abstract. The study of the accountability of social welfare institutions in the Special Region of Yogyakarta in the framework of good corporate governance aims to determine the principle of accountability and the variance of accountability of LKS managers towards related stakeholder. This research description provides an overview of the accountability principles of social welfare institutions as public institutions from the aspects of legal accountability and honesty, managerial accountability, program accountability, policy accountability, and financial accountability. The qualitative research method explores the sample of student worksheets with the first rank of the DIY level. The research subjects were determined by purposive sampling of student worksheet with DIY level. The data were collected by in-depth interviews, in-depth observation and literature study. Everything is integrated into the analytical content. Data credibility validation through triangulation. validation of results followed by transferability, dependability and conformability tests. The results showed that managerial accountability and program accountability tended to be passive, managerial accountability and program accountability were low, financial accountability was closed and accountability of policy was relative. The courage to run GCG LKS depends on the attitude of the BOD. Even though the research was conducted for 8 years, this research still has weaknesses, it is recommended that further research with a personal approach to the founders and BOD, so that researchers can analyze the relationship between the founders and BOD. The research implication is reflective material for policymakers to evaluate BOD, managers, volunteers and LKS donors.Abstrak. Penelitian akuntabilitas lembaga kesejahteraan sosial di Daerah Istimewa Yogyakarta dalam kerangka good corporate governance bertujuan untuk mengetahui prinsip akuntabilitas dan varian akuntabilitas pengelola LKS terhadap stakeholder terkait. Deskripsi penelitian memberikan gambaran mengenai prinsip akuntabilitas lembaga kesejahteraan sosial sebagai lembaga publik dari aspek akuntabilitas hukum dan kejujuran, akuntabilitas manajerial, akuntabilitas program, akuntabilitas kebijakan, dan akuntabilitas finansial. Metode penelitian kualitatif eksplorasi sampel LKS berprestasi peringkat pertama tingkat DIY. Subjek penelitian ditentukan purposive sampling LKS berprestasi tingkat DIY, data dikumpulkan dengan wawancara mendalam, observasi mendalam dan studi pustaka. Semua ada diintegrasi dalam konten analisis. Validasi data credibility melalui triangulasi. validasi hasil dilanjutkan dengan uji transferability, dependability dan conformability. Hasil penelitian menunjukkan akuntabilitas manajerial dan akuntabilitas program cenderung pasif, akuntabilitas manajerial dan akuntabilitas program bersifat rendah, akuntabilitas finansial bersifat tertutup, akuntabilitas kebijakan bersifat relatif. Keberanian menjalankan GCG LKS tergantung dari sikap BOD. Walaupun penelitian dilakukan selama 8 tahun, penelitian ini masih ada kelemahan, disarankan penelitian lanjutan dengan pendekatan personal kepada para pendiri dan BOD, sehingga peneliti dapat menganalisis hubungan antara pendiri dengan BOD. Implikasi penelitian menjadi bahan refleksi bagi pengambil kebijakan untuk mengevaluasi BOD, pengelola, relawan dan para donatur LKS.